The Effect of Hominis Placenta Herbal Acupuncture on Bell's palsy - Yun Jeong-hun; Yook Tea-han; Song Beom-yong (Korean Pharmacopuncture Institute, 2000)
This report was done to observe the effect of Hominis placenta herbal acupuncture on Bell's palsy. The study group comprised 16 patients who arrived at Woo-suk university oriental hospital from January, 1999 till January, 2000 for Bell's palsy. All patients were divided into two group. One was herbal acupunture group, and the other was control group. Acupunture group was done herbal acupuncture therapy on the facial acupuncture points. Followings are achievement and a term of each group. In herbal acupuncture group, 100% motor recovery was 7 case, 75% was 1 case, and 25% motor recovery term was 7.38±5.21 days, 50% was 11.00±6.16 days, 75% was 15.13±9.55 days, 100% was 23.14±7.97 days. In control group, 100% motor recovery was 4 case, 75% was 2 case, 25% below was 2 case and 25% motor recovery term was 11.17±4.96days, 50% was 18.17±6.82 days, 75% was 29.50±6.95 days, 100% was 44.00±11.49 days. The above results indicate that Hominis placenta herbal acupuncture is a useful effect on Bell's palsy. thus, continuous herbal acupunture study will be needed for more clinical application on Bell' palsy.